DEVELOPING VOCABULARY MASTERY THROUGH WORD ASSOCIATION BY THE SECOND YEAR STUDENTS OF SMP MUHAMMADIYAH AL AMIN SORONG - Ruslan Ruslan (Qalam : Jurnal Ilmu Kependidikan, 2017)
AbstractThis research was conducted with the aim of proving that teaching English through word association can develop the vocabulary of the second year students of SMP Muhammadiyah Al Amin Sorong. The sample of the research was 31 students in VIII A class at SMP Muhammadiyah Al Amin Sorong. In collecting the data he used tests (Pre-test and Post-test). The research applied pre-test and post-test one group design. The instrument of data collection was a test. The data analyzed statistically. The result of the data analysis has shown that there was a significant difference between the results of pre-test and post-test. It was proved through the testing hypothesis, i.e. applying 0.05 level significance with 30 (31-1) the degree of freedom (df), the researcher found that t-test (7.3) was greater than the value of the t-table (1.697). In conclusion, the word association was effective to be used in teaching English Vocabulary.Â